2019
DOI: 10.1007/s40430-019-1619-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homogeneous–heterogeneous reactions and non-Fourier heat flux theory in Oldroyd-B fluid with variable conductivity

Abstract: This article scrutinizes the influence of chemical reactions on flow of an Oldroyd-B fluid due to stretched cylinder. In vision of non-Fourier heat flux model, the heat transfer phenomenon is scrutinized. This enhanced constitutive model anticipates the time space upper-convected derivative which is recycled to depicting heat conduction mechanism. Additionally, heat transfer scrutiny is considered with the influence of thermal conductivity which is temperature dependent. Apposite conversions are engaged to acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…29 analyzed the radiative flow of micropolar fluid with a magnetic effect over a stretching sheet. The MHD flow of Casson fluid with heating influence was presented by Tassaddiq et al 30 Further related studies are mentioned in Abel et al, 31 Waqas et al, 32 Irfan et al, 33 Rajagopal, 34 and Alamri et al 35 In light of the overhead declared studies, we anticipated the analytical study of time-dependent non-Newtonian Maxwell fluid with Cattaneo-Christov theory through an extending cylinder. The non-uniform heat source/sink, variable thermal conductivity, Brownian motion, and thermophoresis phenomena are operated.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…29 analyzed the radiative flow of micropolar fluid with a magnetic effect over a stretching sheet. The MHD flow of Casson fluid with heating influence was presented by Tassaddiq et al 30 Further related studies are mentioned in Abel et al, 31 Waqas et al, 32 Irfan et al, 33 Rajagopal, 34 and Alamri et al 35 In light of the overhead declared studies, we anticipated the analytical study of time-dependent non-Newtonian Maxwell fluid with Cattaneo-Christov theory through an extending cylinder. The non-uniform heat source/sink, variable thermal conductivity, Brownian motion, and thermophoresis phenomena are operated.…”
Section: Introductionmentioning
confidence: 80%
“…The MHD and viscous dissipative flow of micropolar nanofluid through an extending sheet was analyzed by Hsiao. 22 The MHD Maxwell fluid through an extending surface was considered by Abel et al 23 The Oldroyd-B nanofluid flow with mass and thermal stratification conditions was inspected by Waqas et al 24 The Oldroyd-B fluid flow with CCT and HHR under the impact of nonlinear thermal conduction was studied by Irfan et al 25 The MHD Williamson nanofluid flow through a nonlinear extending plate was presented by Dawar et al 26 The MHD non-Newtonian nanofluid flow through two dissimilar geometries with Joule heating was presented by Dawar et al 27 The MHD Jeffrey fluid flow with Hall and ion slip influences inspected by Krishna. 28 Khader and Sharma.…”
Section: Introductionmentioning
confidence: 99%
“…The particles themselves could be porous or nonporous or may become porous during the reaction. They may also change their size, and significant alterations in the structure might accompany the chemical reaction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its extensive applications in the industrial systems, biochemical systems and catalysis, the homogeneous/heterogeneous mixture of chemical reaction systems has received tremendous attention from researchers. The work related to the chemical reaction can be found in the studies reported in References [3339].…”
Section: Introductionmentioning
confidence: 99%